Assessment of marine debris in seagrass beds of Pramuka Island, Kepulauan Seribu. Issue 1 (January 2022) - Rasyid, N; Munir,; Andryan, D; Bengen, D G; Subhan, B
Abstract: Indonesia is referred as the second largest contributor of marine debris in the world after China, with an estimated 0.48-1.29 million metric tons per year. High anthropogenic activities from locals and tourists can produce large marine debris and impact the seagrass ecosystem. This research aimed to identify marine debris in the habitat of seagrass beds on Pramuka Island. Extensive surveys include observing seagrass community structures, the measurement of chemical and physical parameters of the water, and marine debris inventory at three stations in Pramuka Island. Observation results found six seagrass species, with coverage ranged from 1.67-47.32% while the density 28-112.76 stand/m 2 . Marine debris can be classified into six types: plastic, metal, rubber, glass, organic matter, and others. The weight of marine debris for each type ranges from 0.03–2.38 kg. In addition, microplastic found consisted of fiber, film, and fragment with a unit weight of 20–440 particles/kg. In conclusion, the seagrass conditions of each station are classified as damaged. The marine debris that has the most impact on the seagrass beds is plastic. Fiber type microplastic has the most abundance. this can interfere with respiration and the photosynthesis process of seagrass.